2019
DOI: 10.17265/1934-7359/2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Functionality between Virtual Reality and Mixed Reality for Architecture and Construction Uses

Abstract: Virtual Reality (VR) and Mixed Reality (MR) offer unique opportunities for the architecture and construction industry through different approaches with building information modeling (BIM). While VR offers architecture and construction practitioners the ability to personally experience the built environment in an immersive, MR with its unique ability of overlaying digital information in the real world allows practitioners to perform on-site visualization for construction planning and as-built verification. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…In the vast majority of cases, the programming of the sensor has been carried out, considering individual project specifications due to the lack of standards [28][29][30]. The particular solutions developed have been determined to improve specific practices and/or subjects at the teaching or professional level [31][32][33], including architecture [34][35][36][37]. In all these practices, one key concept of VR systems is the "presence", which has been defined as "the sense of 'being' in the VR world" [38].…”
Section: Virtual Reality Systems: Main Issuesmentioning
confidence: 99%
“…In the vast majority of cases, the programming of the sensor has been carried out, considering individual project specifications due to the lack of standards [28][29][30]. The particular solutions developed have been determined to improve specific practices and/or subjects at the teaching or professional level [31][32][33], including architecture [34][35][36][37]. In all these practices, one key concept of VR systems is the "presence", which has been defined as "the sense of 'being' in the VR world" [38].…”
Section: Virtual Reality Systems: Main Issuesmentioning
confidence: 99%
“…The practical application of using AR software and devices has not been sufficiently explored. This research expands on previous studies on the integration process (DaValle and Azhar, 2020; Alizadehsalehi et al , 2020; Prabhakaran et al , 2020) and AR application evaluation (Huang et al , 2019; Huang, 2020) with an in-depth study on superimposing techniques. Although much prior research has established the process for integrating BIM and AR, this research addresses the need for more precise superimposing and examines the integration of BIM and AR from a practical point of view.…”
Section: Introductionmentioning
confidence: 70%
“…Huang reviewed commercial hardware and software of VR and AR for AEC usage. 71 Olbina and Glick applied VR and AR to the field of construction management education, and they found that VR performed better than AR regarding all measured indicators. 72 Another research group reviewed AR and VR applications in architectural design and proposed an alternative system including both AR and VR.…”
Section: Comparing Xr Technologiesmentioning
confidence: 99%
“…Lastly, some scholars compared AR and VR in the AEC domain specifically. Huang reviewed commercial hardware and software of VR and AR for AEC usage 71 . Olbina and Glick applied VR and AR to the field of construction management education, and they found that VR performed better than AR regarding all measured indicators 72 .…”
Section: Related Workmentioning
confidence: 99%